PENGARUH MANAJEMEN STRES DENGAN TEHNIK RELAKSASI NAFAS DALAM TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUSDI WILAYAH KERJA PUSKESMAS SUNGAI IYU ACEH TAMIANG TAHUN 2018 - Nora Hayani; Zulkarnaini Zulkarnaini; Azwarni Azwarni (Jurnal Inovasi Penelitian, 2021)
Relaxation therapy is equivalent to its meaning with both oral and insulin-lowered blood sugar-lowering drugs. Breath relaxation techniques to help relieve stress in Diabetes Mellitus patients so that it can help reduce blood sugar levels, this is in accordance with the opinion of Surwit et al in Kuswandi (2012), which states that stress management techniques when accompanied by standard treatments can help reduce levels blood glucose. The reduction achieved was also almost as big as the expected results of diabetes control drugs. This study aims to determine the effect of deep breath relaxation techniques on the reduction of blood sugar levels in people with diabetes mellitus. The bivariate analysis of this study used the t-test dependent formula with a confidence level of 95% with a value of α 0.05. The results of the study of blood sugar levels in patients with diabetes mellitus before and after breathing relaxation techniques using paired T-Test samples obtained a significant value of 0.07, ie there was no effect of deep breathing relaxation techniques on reducing blood sugar levels in people with diabetes mellitus in the Sungai Puskesmas Working Area Iyu. but the results of this study show a decrease in blood sugar levels after performing deep breathing relaxation techniques. It is expected that the health department will develop and implement the quality of nursing services for patients with diabetes mellitus by intervening in deep breathing relaxation techniques.